Electron beam induced evolution in Au, Ag, and interfaced heterogeneous Au/Ag nanoparticles. Issue 32 (27th July 2015) - Liu, Yuzi; Sun, Yugang
Abstract : A sintering process of nanoparticles made of Ag, Au, and interfaced Ag/Au heterodimers was investigated by in situ transmission electron microscopy at room temperature. Abstract : A sintering process of nanoparticles made of Ag, Au, and interfaced Ag/Au heterodimers was investigated by in situ transmission electron microscopy at room temperature. Such a process is driven by the illumination of a high-energy electron beam accelerated at 200 kV that promotes atom diffusion in the nanoparticles that are in physical contact. Upon electron illumination, adjacent Au nanoparticles gradually merge together to form a larger particle along with the reduction of the surface area despite the fact that orientated attachment is not observed. According to the detailed analysis of the size change of the particles and the contact area, it was found that the nanoparticle fusion process is significantly different from the well-established thermal diffusion mechanism. In addition to the similar fusion process of Au nanoparticles, Ag nanoparticles undergo apparent sublimation induced by knock on damage because the transferred energy from the electron beam to nanoparticles is higher than the surface binding energy of Ag atoms when the electron scattering angle is larger than 112°. The particles with a smaller size diffuse faster. Surface diffusion dominates at the beginning of the fusion process followed by slower lattice diffusion. Electron beam illumination can transform the interfaced Au/Ag dimers to Au@Ag core–shell particles followed by a slow removal of the Ag shells. This process under normal electron beam illumination is a lot faster than the thermally driven process. Both diffusion and sublimation of Ag atoms are dependent on the intensity of the electron beam, i.e., a higher beam intensity is favorable to accelerate both the processes.